Tempskya in the Valanginian of South America (Mulichinco Formation, Neuquén Basin, Argentina) - Systematics, palaeoclimatology and palaeoecology - Martinez, Leandro Carlos Alcides (2015)
New specimens of the tree fern Tempskya are described from the Mulichinco Formation (Valanginian), Neuquén Basin, Argentina. Tempskya is a genus for permineralized false fern trunks. This extinct genus had a wide distribution during the Early Cretaceous. However, records from the Southern Hemisphere are scarce and restricted to the late Early Cretaceous in Argentina and Australia. The Patagonian specimens here described from the Valanginian represent the oldest record of this genus. The presence of this fossil fern implies humid and warm climatic conditions during the deposition of the Mulichinco Formation in the Early Cretaceous. The new specimens show petioles, leaf remains, sporangia and spores. On the basis of these new features, a new systematic position for Tempskya is suggested.